2017
DOI: 10.1016/j.jamda.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Is Associated With Higher Frailty Risk in Older People: An 8-Year Longitudinal Cohort Study

Abstract: Objective To investigate whether polypharmacy is associated with a higher incidence of frailty in a large cohort of North Americans during 8 years of follow-up. Design Longitudinal study, follow-up of 8 years. Participants A total of 4402 individuals at high risk or having knee osteoarthritis free from frailty at baseline. Measurements Details regarding medication prescription were captured and categorized as 0–3, 4–6, and ≥7. Frailty was defined using the Study of Osteoporotic Fracture index as the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
125
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 37 publications
16
125
3
7
Order By: Relevance
“…139 Likewise, in a cohort study of community-dwelling people aged between 50 and 75 years, Saum et al observed a dose-response association, with an OR of 2.30 for polypharmacy (95% CI 1.60-3.31) and 4.97 for hyperpolypharmacy (95% CI 2.97-8.32). 141 These observational studies provide evidence that polypharmacy is a risk factor for frailty. Over the follow-up period, participants taking four to six medications were more likely to become frail than those taking zero to three medications were, and this likelihood was even higher in those taking seven or more medications.…”
Section: Explanationmentioning
confidence: 97%
“…139 Likewise, in a cohort study of community-dwelling people aged between 50 and 75 years, Saum et al observed a dose-response association, with an OR of 2.30 for polypharmacy (95% CI 1.60-3.31) and 4.97 for hyperpolypharmacy (95% CI 2.97-8.32). 141 These observational studies provide evidence that polypharmacy is a risk factor for frailty. Over the follow-up period, participants taking four to six medications were more likely to become frail than those taking zero to three medications were, and this likelihood was even higher in those taking seven or more medications.…”
Section: Explanationmentioning
confidence: 97%
“…These results may have limited generalizability to the US population because US‐based frailty research showed that prevalence varies by race, socioeconomic status, and geographic area . To our knowledge, only one US‐based cohort, the Osteoarthritis Initiative, examined this association . However, it measured frailty using the Study of Osteoporotic Fracture index, which limits comparisons with studies that use more common frailty measures.…”
mentioning
confidence: 99%
“…Results from longitudinal analyses of polypharmacy and frailty were reported; however, these studies were primarily conducted in non‐US regions including Australia, China, and Europe . These results may have limited generalizability to the US population because US‐based frailty research showed that prevalence varies by race, socioeconomic status, and geographic area .…”
mentioning
confidence: 99%
“…The rapid development of biological drugs will require the geriatrician to be an expert on these emerging drugs and their side-effects, e.g., antibodies against myostatin or activin receptors to treat sarcopenia (8). Geriatricians are already aware of the problems produced by polypharmacy and inappropriate drug use in older persons (9)(10)(11)(12)(13)(14)(15)(16)(17), and this will only become worse with the interactions with biologics which will only become obvious after many years of use. All of this will drive geriatricians to become prime users of personalized (P4) medicine (i.e., predictive, preventive, personalized and participatory), assisted by computers (18).…”
mentioning
confidence: 99%